Do Civil and Political Repression Really Boost Foreign Direct Investments? - Philipp Harms; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2001)
Multinational enterprises are often accused to have a preference for investing in countries in which the working populations' civil and political rights are largely disregarded. This paper presents an empirical investigation of the popular political repression boosts FDI hypothesis and arrives at the conclusion that the hypothesis is not supported. On the contrary, multinational enterprises rather appear to be attracted by countries in which civil and political freedom is respected. Our finding thus supports the notion that there is a positive relationship between democracy and economic growth.
Keywords: 330; Foreign direct investment; globalization; globalisation; democracy; freedom